1985
DOI: 10.1172/jci112003
|View full text |Cite
|
Sign up to set email alerts
|

Antiadhesive properties of biological surfaces are protective against stimulated granulocytes.

Abstract: When tested on endothelial cell-derived extracellular matrices, neutrophils again showed functional nonresponsiveness to Nformnyl-Met-Leu-Phe. Scanning electron microscopy revealed an impressive congruency between the degree of cellular spreading and metabolic activation iu the presence of N-formylMet-Leu-Phe, with maximally flattened neutrophils on plastic vs. nonspread, polarized cells on monolayers. Identical results were obtained by using other adhesion inducers such as complement-activated plasma or endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…The engagement of adhesion receptors induces an initial suppression of ROS formation, resulting in a dramatically delayed oxidative response to a number of stimuli, such as fMLF and TNF-␣ (13,14,37). This delayed response is thought to correspond to the in situ situation, in which inappropriate ROS formation is inhibited to prevent tissue damage when cells are migrating through the tissue to inflammatory sites.…”
Section: Discussionmentioning
confidence: 99%
“…The engagement of adhesion receptors induces an initial suppression of ROS formation, resulting in a dramatically delayed oxidative response to a number of stimuli, such as fMLF and TNF-␣ (13,14,37). This delayed response is thought to correspond to the in situ situation, in which inappropriate ROS formation is inhibited to prevent tissue damage when cells are migrating through the tissue to inflammatory sites.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence that engagement of adhesion receptors can induce a suppression of ROS generation was first provided by Fehr et al (33) and Nathan (3). Nathan showed that adhesion of neutrophils to surfaces coated with ECM proteins (fibronectin, fibrinogen, laminin, and the like) resulted in a dramatically delayed oxidative response to soluble cytokine stimuli (fMLF, TNF-α, and so on).…”
Section: Discussionmentioning
confidence: 99%
“…These conditions bear little resemblance to the stages of inflammation in which PMN stick to endothelium, penetrate basement membranes and migrate through tissues, adherent the whole while to other types ofcells and/or proteins of extracellular matrix. Attempts to analyze the respiratory burst of adherent PMN have been thwarted by the propensity of nonbiologic surfaces to trigger the burst (6), and of biologic surfaces to suppress it (22).…”
Section: Introductionmentioning
confidence: 99%